Posterior Left Atrial Adipose Tissue Attenuation Assessed by Computed Tomography and Recurrence of Atrial Fibrillation After Catheter Ablation - Mohammed El Mahdiui; Judit Simon; Jeff M. Smit; Jurriën H. Kuneman; Alexander R. van Rosendael; Ewout W. Steyerberg; Rob J. van der Geest; Lili Száraz; Szilvia Herczeg; Nándor Szegedi; László Gellér; Victoria Delgado; et al. (2021)
[Figure: see text].